(3eHGOF GdeMGSHI (B:s (3GdGUhd GdYdejI hGdYedjI (B/s - (3OgeT, fYjes ((3YeGf(B: s (3OGQ hGFd(B, s, 2002)
(3jVe GdJShjGJ heHOC GdebGHdI, GdeOjfhf hChQGb GdbHV bUjQI GdCLd, GdGSJKeGQGJ GdeGdjI GdeDbJI HGdGSge hGdSfOGJ, GdeNRhf, GdGUhd GdKGHKI , GdGdJRGeGJ hChQGb GdOaY bUjQI GdCLd, bGFeI GdJOabGJ GdfbOjI, JMdjd GdbhGFe GdeGdjI, GdbjeI GdRefjI ddfbhOs
(3HHdjhZQGajG(B: (3U(B329-331s
Keywords: (3GdeMGSHIs; (3GdfbhOs